Historical precondition and diffi culties of implementation land market in Ukraine - Zhulkanych, Nelya; Mistchanyn, Vasyl (Ukrainian Peasant, 2021)
Introduction. In the conditions of formation of market relations in independent Ukraine the introduction of agrarian in general and land reforms, in particular, became important. An important part of the process of implementation of these transformations is the reform of land relations. The result of the elimination of the state monopoly on land, the establishment of market transformations in the agricultural sector was the introduction of private ownership of agricultural land. Now it remains to implement the preconditions for the ending of agrarian reform - to open the land market. The purpose of the article is to clarify the benefi ts and risks of the introduction of free circulation of agricultural land in Ukraine, the limitation associated with this measure. Results.The article presents a brief retrospective analysis of land relations in Ukraine regarding the implementation of certain elements and components of the land market. Prospects and diffi culties of land market introduction in Ukraine are revealed. Discussion questions on the expediency or inexpediency of opening the market of agricultural lands are analyzed. The positive and negative consequences of this step are considered. In particular, the positives for small and medium-sized businesses in terms of access to cheap mortgage lending secured by land. Among the risks of this process are: sale of Ukrainian lands to foreigners; buying land at a low initial price; lack of opportunity for peasants to compete with large agricultural holdings. The article also analyzed the regulatory and legal restrictions imposed by the state to prevent risks. It is pointed out the need to fi nalize the legislative package for the practical implementation of the regulated land market. Conclusions. The study concluded that the completion of the legislative package and the adoption of these laws to open the land market is necessary to ensure transparency, effi ciency and prevent the monopolization of agricultural land. Also, in the process of introducing a civilized land market in Ukraine, it is worth using foreign experience in reforming the agricultural sector and implementing the principles of land use based on market relations. Considering the foreign experience of opening the market of agricultural land, the positive effect predicted by the World Bank experts, as well as the international obligations undertaken by Ukraine, the introduction of the circulation of agricultural land in Ukraine is considered appropriate. The consequence should be the improvement of land relations and increase the effi ciency of land use.